2023
DOI: 10.1007/s42690-023-00989-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abamectin and fipronil insecticides on the brain and compound eyes of the embryo of Heteracris littoralis (Rambur) (Orthoptera: Acrididae)

Abstract: Chemical pesticides are essentially hazardous. The risks differ from compound to compound, and much of the information on their actions on insect development remains to be captured. The toxicity of abamectin (a macrocyclic lactone, acting on glutamate-gated chloride channels of insects), and fipronil (a phenylpyrazole, disrupting the GABA receptors) was given on embryos of the short-horned grasshopper Heteracris littoralis (Rambur, 1838) for the first time. Abamectin is 66 times more fatal than fipronil. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Abdel Rahman [34] confirmed that abamectin affects the brain and compound eyes of locusts with significant decreases in brain cell numbers, and the protocerebrum, optic lobe, deutocerebrum, and tritocerebrum of the brain all being deformed and shrunken in treated embryos. In insects treated with abamectin, the brain's neurosecretory system showed a buildup of stainable material in the corpora cardiaca and neuropilar storage areas, which was linked to an absence of ovarian development [35].…”
Section: Discussionmentioning
confidence: 88%
“…Abdel Rahman [34] confirmed that abamectin affects the brain and compound eyes of locusts with significant decreases in brain cell numbers, and the protocerebrum, optic lobe, deutocerebrum, and tritocerebrum of the brain all being deformed and shrunken in treated embryos. In insects treated with abamectin, the brain's neurosecretory system showed a buildup of stainable material in the corpora cardiaca and neuropilar storage areas, which was linked to an absence of ovarian development [35].…”
Section: Discussionmentioning
confidence: 88%